SA ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR KINERJA PERUSAHAAN CV MULTI MEDIKA SUKSESINDO SELAMA NORMAL BARU - Shalma Azhahra (Administraus, 2021)
Abstract : This research was conducted at the company CV Multi Medika Suksesindo, which is a company engaged in the health industry. This study aims to look at financial reports in measuring company performance that are still running during the new normal due to the Covid-19 pandemic. To see whether the company's financial condition is in good condition, various analyzes can be carried out, one of which is ratio analysis. The population in this study is the company's actual data and the samples taken are the financial reports of June, July, August and the data analysis techniques used are financial ratios (liquidity, solvency, profitability, and activity). The data source obtained from the owner of CV Multi Medika Suksesindo which has been processed. Based on the monthly liquidity ratio, it is in a stable condition so that the condition is categorized as good (liquid). The solvency ratio shows that the company's capital is still sufficient to guarantee the debt given by creditors so that the situation is said to be in good condition (can be resolved). Judging by the activity ratio, it shows an increase every month so that things are said to be in good condition. The profitability ratio shows an increase from month to month, so it can be said that the company is in a stable state during the new normal June to August 2020. Keywords: Financial statement analysis, new normal, company performance   Abstrak : Penelitian ini dilakukan pada perusahaan CV Multi Medika Suksesindo, yang merupakan perusahaan yang bergerak diindustri kesehatan. Penelitian ini bertujuan untuk mengetahui laporan keuangan dalam mengukur kinerja perusahaan yang masih berjalan selama normal baru akibat pandemik Covid-19. Untuk mengetahui apakah keadaan keuangan perusahaan dalam kondisi yang baik dapat dilakukan berbagai analisa, salah satunya adalah analisis rasio. Populasi dalam penelitian ini adalah data actual perusahaan dan sampel yang diambil adalah laporan keuangan bulan Juni, Juli, Agustus serta teknik analisis data yang digunakan adalah rasio keuangan (likuiditas, solvabilitas, profitabilitas, dan aktivitas). Sumber data penelitian diperoleh dari pemilik CV Multi Medika Suksesindo yang telah diolah. Berdasarkan rasio likuiditas setiap bulannya mengalami keadaan stabil sehingga keadaan perusahaan dikategorikan dalam keadaan baik (liquid). Dari rasio solvabilitas menunjukkan bahwa modal perusahaan masih mencukupi untuk menjamin hutang yang diberikan oleh kreditor sehingga keadaan perusahaan dikatakan dalam keadaan baik (solveable). Ditinjau dengan rasio aktivitas menujukkan peningkatan di setiap bulannya sehingga keadaan perusahaan dikatakan dalam keadaan baik. Ditinjau dari rasio profitabilitas menunjukkan adanya peningkatan dari bulan ke bulan sehingga dapat dikatakan keadaan perusahaan berada dalam keadaan stabil selama normal baru bulan Juni hingga Agustus 2020. Kata Kunci : Analisis Laporan Keuangan, Normal Baru, Kinerja Perusahaan